Identity Politics and Polarization in Contemporary Muslim Countries: The Impact of Elections, Social Media, and Global Dynamics - Helena Octavianne; Fendy Suhariadi; Mohammad Fakhruddin Mudzakkir; Donny Trianto; Umar Chamdan (Faculty of Sharia, IAIN Metro, 2024)
This article examines the growing influence of identity politics and polarization in contemporary Muslim countries, focusing on the impact of elections, the widespread role of social media, and global dynamics. As political systems in the Muslim world become more fragmented, identity-based movements—often rooted in ethnic, religious, or sectarian affiliations—have gained significant prominence. These dynamics have heightened political polarization when intertwined with electoral processes, shaping voter behaviour and policymaking. The rise of social media has further transformed political engagement, both as a platform for grassroots activism and a tool for spreading misinformation that deepens societal divisions. This research uses a qualitative approach with literature analysis to explore the relationship between identity politics and polarization in contemporary Muslim countries, focusing on elections, social media, and global dynamics. The findings highlight the urgent need for effective strategies to reduce polarization and promote inclusive governance. Often fueled by identity-based divisions and amplified by social media, polarisation poses serious threats to political and social stability. In today's interconnected world, these divisions extend beyond local and national politics, influencing international relations and regional security. Addressing these challenges requires a comprehensive approach that fosters open dialogue, strengthens democratic institutions, counters misinformation, and raises public awareness to bridge societal gaps. Inclusive governance also demands policies that engage marginalized groups, ensuring fair representation and addressing the root causes of polarization. By adopting these measures, Muslim-majority countries can work toward more excellent political stability and social cohesion.